YIELD PERFORMANCE AND STABILITY OF CASTOR (Ricinus communis L.) ACROSS MULTIPLE ENVIRONMENTS IN INDIA (Applied Biological Research, 2025)
Twelve castor genotypes were evaluated across ten environments in India during kharif 2022 to assess the genotype performance and to identify the stable and high-yielding genotypes. Genotype plus genotype × environment interaction (GGE) biplot for seed yield was employed to evaluate the genotype × environment interaction (GEI). The polygon view of GGE biplot revealed the "which-won-where" pattern of genotypes across different environments. Genotypes with the shortest vectors from the average environmental coordinates (AEC) line were identified as highly stable across the test environments, exhibiting higher mean seed yield per hectare. These findings indicate that certain genotypes possess both higher seed yield potential and stability across diverse environments, as demonstrated by GGE biplot analysis.
Keywords: AMMI; genotype x environment interaction; GGE-biplot; Ricinus communis; stability